Comparative experimental study of the biomechanical properties of retrograde tibial nailing and distal tibia plate in distal tibia fracture - Lin, Xuping; Zhang, Cong; Yang, Yanfang; Yang, Wencheng; Wang, Xiaomeng; Lu, Haichuan; Liu, Qingjun (Frontiers in Bioengineering and Biotechnology, 2024)
Objective A biomechanical comparative analysis was conducted to evaluate the retrograde tibial nailing (RTN) and distal tibia plate techniques for the treatment of distal tibia fractures. Methods Fourteen fresh adult tibia specimens were selected, consisting of seven males and seven females aged 34–55 years. The specimens were randomly divided into two groups (Group A and Group B) using a numerical table method, with seven specimens in each group. Group A underwent internal fixation of distal tibial fractures using RTN, while Group B received internal fixation using a plate. The axial compression properties of the specimens were tested in the neutral positions under pressures of 100, 200, 300, 400, and 500 N. Additionally, the torsional resistance of the two groups was assessed by subjecting the specimens to torques of 1.0, 2.0, 3.0, 4.0, and 5.0 N·m. Results At pressures of 400 and 500N, the axial compression displacement in Group A (1.11±0.06, 1.24±0.05) mm was significantly smaller than that in Group B (1.21±0.08, 1.37±0.11) mm (P = 0.023, 0.019). Moreover, at a pressure of 500N, the axial compression stiffness in Group A (389.24±17.79) N/mm was significantly higher than that of the control group (362.37±14.44) N/mm (P= 0.010). When subjected to torques of 4 and 5 N·m, the torsion angle in Group A (2.97°±0.23°, 3.41°±0.17°) was significantly smaller compared to Group B (3.31°±0.28°, 3.76°±0.20°) (P=0.035, 0.004). Furthermore, at a torque of 5N·m, the torsional stiffness in Group A (1.48±0.07) N·m/° was significantly higher than that in Group B (1.36±0.06) N·m/° (P=0.003). Conclusion The results obtained from the study demonstrate that the biomechanical performance of RTN outperforms that of the distal tibial plate, providing valuable biomechanical data to support the clinical implementation of RTN.